Age factors in biometric processing - Fairhurst, Michael 1948- (The Institution of Engineering and Technology, 2013)
The book covers the following areas: ageing; biometrics; social considerations; ethical considerations; online signature; fingerprints; human inspection; forensics; face image; age prediction; and face recognition.